POTRET IMPLEMENTASI WEBSITE LAPOR! PADA INSTANSI DINAS KOPERASI, USAHA KECIL DAN MENENGAH PROVINSI JAWA TIMUR - Prameswari, Sartika Devi; Wahyudi, Kalvin Edo (Universitas Jabal Ghafur, 2024)
The Cooperative, Small and Medium Enterprises Agency of East Java Province (Diskop and SMEs East Java) has successfully integrated complaint services through the LAPOR! website, demonstrating the effectiveness of e-Government implementation. Established under East Java Governor Regulation No. 86 of 2016, Diskop and SMEs utilize this online platform to enhance public service quality through technology. The complaint management process, from reception to monitoring, ensures prompt responses and appropriate solutions. Through information and communication technology, such as SMS, websites, and mobile applications, interaction between the public and the government is facilitated. Quick responses, integration with government agencies, and the use of technology as a tool for better public service showcase the effectiveness of e-Government. Diskop and SMEs create an environment where the public can easily voice complaints, supporting transparency and enhancing public trust. As a good example of e-Government implementation, Diskop and SMEs in East Java strengthen the foundation of e-Government, create improved public services, and increase public trust and participation in the government administrative processKeywords : E-Government, Public Service, Website LAPOR!